2022
DOI: 10.3390/coatings12040484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleurotus ostreatus on Physicochemical Properties and Residual Nitrite of the Pork Sausage

Abstract: In this work, a novel sausage incorporated with the Pleurotus ostreatus (PO) puree was successfully developed to reduce the residual nitrite and lipid oxidation during refrigerated storage (4 ± 1 °C) for 20 days. Five recipes with the supplement proportion of 0 wt.%, 10 wt.%, 20 wt.%, 30 wt.%, and 40 wt.% PO were produced and their physicochemical properties, nitrite residue, and sensory characteristics were measured. The results show that the content of moisture and all the essential amino acids (especially l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…This finding was in line with the results from Husain and Huda-Faujan [20] on the Imitation Chicken Nugget (ICNs) from oyster mushroom (Pleurotus ostreatus) stems and chickpea flour where the fat content of ICNs ranged from 0.47% to 0.62% were lower than the fat content of control nugget samples (1.30%). In addition, similar results were also reported in the declining pattern of fat content from 17.60% to 14.82% on sausage incorporated with the increasing amount of Pleurotus ostreatus [21]. In fact, the fat content of edible mushrooms (Pleurotus ostreatus) was 1.50% [22], while the fat content of Indian scad (Decapterus russelli) was recorded as less than 4.00% [23].…”
Section: A Proximate Compositionsupporting
confidence: 71%
“…This finding was in line with the results from Husain and Huda-Faujan [20] on the Imitation Chicken Nugget (ICNs) from oyster mushroom (Pleurotus ostreatus) stems and chickpea flour where the fat content of ICNs ranged from 0.47% to 0.62% were lower than the fat content of control nugget samples (1.30%). In addition, similar results were also reported in the declining pattern of fat content from 17.60% to 14.82% on sausage incorporated with the increasing amount of Pleurotus ostreatus [21]. In fact, the fat content of edible mushrooms (Pleurotus ostreatus) was 1.50% [22], while the fat content of Indian scad (Decapterus russelli) was recorded as less than 4.00% [23].…”
Section: A Proximate Compositionsupporting
confidence: 71%
“…El-Refai et al (2014) were also found that sensory analysis of 8 % (w/w) P. ostreatus added beef meatballs had good sensory characteristics. Wu et al (2022) reported that Sausage containing P. ostreatus had better sensory scores than sausage samples without P. ostreatus (Wu et al 2022).…”
Section: Sensory Analysismentioning
confidence: 99%